Long-Term Outcome and Complications after Transcondylar Screw Placement for Canine Humeral Intracondylar Fissure - Low, Daniel; Hutchings, Victoria; Rutherford, Scott (Veterinary and Comparative Orthopaedics and Traumatology, 2024)
Objective The aim of this study was to report postoperative complications and long-term outcomes following transcondylar screw placement for humeral intracondylar fissure (HIF).Study Design It was a retrospective single-centre case series. Medical records (2018–2022) were reviewed for dogs with HIF treated with transcondylar screw placement. Data collected included signalment, concurrent orthopaedic disease, partial or complete HIF, surgeon, surgical approach, surgical technique and implant type, transcondylar screw angulation, postoperative complications and outcomes. Long-term outcome was assessed with owner questionnaire, orthopaedic examination and follow-up radiography. Statistical analysis was performed to identify risk factors predisposing to a complication or a poor outcome.Results Forty-seven dogs (57 elbows) met the inclusion criteria; long-term follow-up was available in 41 dogs (50 elbows). Minor and major medical complications were noted in seven and three elbows respectively. The total complication rate was 17.5%. Increasing age was significantly associated with a reduced risk of postoperative complications (p = 0.0051). No other risk factors were identified. A postoperative complication was not associated with a less than full outcome (p = 0.5698).Conclusion Transcondylar screw placement for HIF is associated with a low complication rate and good outcome.
Keywords: humeral intracondylar fissure; transcondylar screw; complication; outcome